O estudo do código bibliográfico nas edições da segunda metade do século XIX de papéis avulsos de Machado de Assis - Patueli, Fabiana da Costa Ferraz (2010)
The researsh intends to be the study of codes of bibliographic editions of the Papéis Avulsos' Machado de Assis, published in the second half of the century XIX, to be evedent the ideas that permeate the practice of publishing, typesetting and copyright in publication in book and periodicals, and adjacent ideas these practices